Facility usage and personal training support at JISS training gym - Oishi, M. (Journal of High Performance Sport, 2020)
At the Japan Institute of Sports Sciences training gym, the use of para-athletes began in stages from 2015, we are working hard to improve the performance of para-athletes through individual training support. In this paper, after describing preparations for the first trial FC implementation that was accepted and considerations after the implementation, the facility use status of the para-athletes of the training gym and the summary and characteristics of individual training support are described.